2015
DOI: 10.1186/s12879-015-0905-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine reverses drug resistance in isoniazid and ethambutol dual drug-resistant Mycobacterium tuberculosis clinical isolates

Abstract: BackgroundTetrandrine is a natural chemical product purified from fourstamen stephania root which recently has been shown to act similarly as synthesized drug efflux pump inhibitor verapamil. The aim of the study is to examine whether tetrandrine could potentiate anti-tubercular drugs to which Mycobacterium tuberculosis (MTB) has turned resistant via efflux mechanisms.MethodsWe screened 200 MTB clinical isolates using drug sensitivity test to look for those who have turned resistant to the drugs most probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Calcium antagonists improved in vitro activities of tetracycline and fluoroquinolones against S. aureus, Enterobacteriaceae and non-fermenters irrespective of whether the strains were tetracycline-or fluoroquinolone-resistant [158][159][160]. It also improved activities of ofloxacin, rifampicin, and bedaquilin, but not isoniazid or amikacin against M. tuberculosis as well as M. abscessus (Table 3) [ [161][162][163][164][165][166][167][168][169]. Verapamil also increased the intraphagocytic activities of isoniazid and rifampicin [168] as well as bedaquilin and moxifloxacin [168] against drug-susceptible and drug-resistant M. tuberculosis and also the intracellular activity of azithromycin against L. monocytogenes [170,171] and that of daptomycin against S. aureus [172].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Calcium antagonists improved in vitro activities of tetracycline and fluoroquinolones against S. aureus, Enterobacteriaceae and non-fermenters irrespective of whether the strains were tetracycline-or fluoroquinolone-resistant [158][159][160]. It also improved activities of ofloxacin, rifampicin, and bedaquilin, but not isoniazid or amikacin against M. tuberculosis as well as M. abscessus (Table 3) [ [161][162][163][164][165][166][167][168][169]. Verapamil also increased the intraphagocytic activities of isoniazid and rifampicin [168] as well as bedaquilin and moxifloxacin [168] against drug-susceptible and drug-resistant M. tuberculosis and also the intracellular activity of azithromycin against L. monocytogenes [170,171] and that of daptomycin against S. aureus [172].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Researchers attributed the emergence of resistance to several factors, including poor compliance to a course of prescribed medications, inconsistent monitoring, medication abuse, and mutations in strains. Resistance can also develop due to change in membrane pumps, changes in the interaction of the drug or target, and chromosome mutations [33]. Another reason may include the low permeability of the mycobacterial cell wall due to its lipid-rich nature, which prevents the accessibility of compounds to targets.…”
Section: Emergence and Treatment Of Multi-drug Resistant Tb (Mdr-tb) And Extensively Drug-resistant Tb (Xdr-tb)mentioning
confidence: 99%
“…This study suggested that the combination therapy of tetrandrine with frontline anti‐TB drugs, isoniazid or ethambutol increased the efficacy of the drug and may help in decrease in the drug dosage, thereby minimizing the ill‐effects associated with the drug. 101 However, since there is a lot of ambiguity in the mechanism of action of tetrandrine and its immunogenic potential is mostly unknown; more studies are needed in order to explore its maximum potential in TB cure.…”
Section: Phytochemicals Used In Tuberculosis Therapy With Their Potential Role In Attmentioning
confidence: 99%